2005
DOI: 10.1097/01.pas.0000163360.40357.f1
|View full text |Cite
|
Sign up to set email alerts
|

A Proposal for a New and More Practical Grading Scheme for Pancreatic Ductal Adenocarcinoma

Abstract: There is no uniformly applied grading system for pancreatic ductal adenocarcinoma (DA). The scheme advocated by the WHO is essentially that of Kloppel et al, and is based on the "highest grade" focus. Although it is precise with good prognostic value, it is unfortunately not widely applied, largely because of the lack of recognition and partly because of its complex nature (interpretation of multiple parameters). Furthermore, it is fundamentally different from the one used in Japan, which evaluates the overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 26 publications
2
70
0
Order By: Relevance
“…In terms of grading, as a nonglandular growth pattern, invasive micropapillary carcinoma would qualify as Grade 3 in the recently proposed grading scheme of pancreatic adenocarcinoma, 16 and the survival analysis below supports this impression.…”
Section: Stage and Gradementioning
confidence: 65%
See 1 more Smart Citation
“…In terms of grading, as a nonglandular growth pattern, invasive micropapillary carcinoma would qualify as Grade 3 in the recently proposed grading scheme of pancreatic adenocarcinoma, 16 and the survival analysis below supports this impression.…”
Section: Stage and Gradementioning
confidence: 65%
“…Also, this survival data correlate with the Grade 3 (poorly differentiated) category in the recently proposed grading scheme, which was found to have a median survival of 17 months (confidence interval ¼ 9-25) for Grade 1, 14 months (confidence interval ¼ 12-16) for Grade 2 and 7 months (confidence Interval ¼ 5-9) for Grade 3. This study documents that invasive micropapillary carcinoma, a distinctive tumor type originally Invasive micropapillary carcinomas of the ampullo-pancreatobiliary region S Khayyata et al described in the breast, urinary bladder, lung and salivary glands, 16 does arise in the ampullopancreatobiliary region as well. In the breast, it was reported to occur in 6% of the cases.…”
Section: Clinical Outcomementioning
confidence: 96%
“…We believe that our study is the first Upregulation of ITGB4 in pancreatic cancer Y Masugi et al only morphological but also genomic intratumoral heterogeneity. 24,25 We found that poorly differentiated adenocarcinoma components, including budding cells and solitary infiltrating cancer cells at invasive fronts, frequently display strong diffuse ITGB4 expression. Our findings are compatible with the prior study reporting that ITGB4 expression was somewhat heterogeneous and that abundant expression of ITGB4 was seen in association with invasive fronts.…”
Section: Knockdown Of Itgb4 Decreases Cell Motility In Pda Cellsmentioning
confidence: 99%
“…22 More recently, Adsay has proposed a simpler grading system that parallels the Gleason grading system for prostate cancer. 23 Pancreatic cancers commonly have a combination of well-formed glands as well as individual cells and clusters, resulting in the appearance of both welldifferentiated and poorly differentiated elements in the same carcinoma. In these cases, the carcinoma should be assigned the worst degree of differentiation present in a significant portion of the carcinoma.…”
Section: Figurementioning
confidence: 99%